Electronic Library “Pskoviana” (structure, content, prospects of development) - Bolshakova, Natalia (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The aim of work is generalization of experience of introduction of innovative forms of storage, scientific treatment and publication of expeditionary materials of the Pskov dialectal and folklore- ethnographic archive that is a resource base for many research and educational projects. Formed during the field inspection for many decades and constantly executable archive contains a rich both language and culturological information generator about folk traditions, about the features of way of life, management, perception of the world, traditional and new values of carriers of folk culture of the Pskov region. The funds indicated till recently were unevenly used in scientifically-educational aims. If a dialectal archive during a few decades is a source lexicographic and areal researches, on his base ten of research works is written, including dissertations, then rich potential of folklore part of archive on a row of objective reasons was not exposed. Meantime an audiofund contains the records of works of verbal folk work of different genres: songs (ceremonial and calendar), fairy-tales, fables, legends, descriptions of ceremonies (wedding, baptismal, funeral- mention) etc. In addition, present records also are a base for a study and Pskov folk colloquial speech, as traditional folklore, especially in the verbal genres, is created and exists on dialectal basis. The artistic, historical and cultural value of various in a genre, stylish relation works of folklore does not cause doubts, but also their dialectal independence was not once marked by researchers and collectors. The search of NT used on archived business resulted in creation of e-library of texts of "Pskoviana", the source of that is not published before the archived exclusive. Unlike a traditional e-library, that, as a rule, is a mediator between a user and informative resource, the e-library of texts formed by us is such resource. Structural basis of library is made by the electronic databases created on the genre-thematic founding. Created and in 2012 got testifying to state registration electronic databases on themes: the "Verbal recitals of Great Patriotic war", "Traditional child's folklore", "Fairy-tales of the Pskov area". All three bases are placed on the specialized web-site (http://nocpskoviana.pskgu.ru/index.php). The prospects of development of e-library of texts of regional character of "Pskoviana" are set in next directions. Addition and correction of the formed fragments of library. So, for example, the base sanctified to the military theme, where verbal stories are while presented only, is complemented due to genre expansion: a selection is already executed from the archive of texts of songs and chastushkas on a military theme. Introduction of voice files (wherein they are while absent) supporting the "deciphered" texts. Presently in a state of preparation there is forming of collection of fairy-tales in the format of CD, after the publication of that all voice files containing the Pskov fairy-tales will be placed on a web-site. Thematic expansion enclosures databases, primarily in the development of the themes. Creation of databases, based on areal principle. Presently in the stage of forming there is a local base on one of south districts of the Pskov area – Sebeže, located on a border with Latvia and Belorussia. Decision of complex of the research and practice tasks related to informatization of the archived work, the row of the theoretical questions, related to the area of textual criticism, communicative dialectology, folklore, philological regional science, requires working. Thus, experience showed that for positioning of regional specific of traditional folk culture in her speech forms an e-library of texts is most representative. The form of library, structured and at the same time allowing a high degree of variability, allows you to optimally organize archival data. The applied methodologies showed perspective of select direction in-process with the archived material of high-cube. The complex of works carried out during the row of years in final analysis must result in creation of single accessible electronic archive to the users. But already the e-library of "Pskoviana" formed and now on the basis of the Pskov dialectal and folklore-ethnographic archive executes the functions of reliable storage and presentation of folk speech culture and language of Pskov earth.